Employee Conflict Strategy berdasarkan Tingkat Pendidikan dan Gender Perspektif Teori Thomas-Killman Conflict Mode: Studi di Kantor Pos KCP Nagan Raya Aceh Barat - Murisa, Wadah; Rusdi; Harmen, Hamdi; Hidayat, Muhammad Rahmat (Jurnal Alwatzikhoebillah : Kajian Islam, Pendidikan, Ekonomi, Humaniora, 2024)
This research analyzed 61 employees of the Nagan Raya KCP Post Office using the Thomas-Kilmann instrument and gender Conflict Mode to explore the influence of educational level and gender differences on resilience and differences in perceptions in dealing with conflict. This research is quantitative research by taking data in the field. Based on this research, it is proven that when facing conflict, there are significant differences based on differences in gender and the level of education of respondents as shown by the indicators competing, collaborating, compromising, avoiding and accommodating, all of which have a significance value of <0.05. These findings indicate that the complexity of the relationship between education and gender can be the basis for a company's policy to formulate policies according to the company's needs and work environment.